2017
DOI: 10.1007/s00520-017-3612-0
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and positive affect in Chinese and United States breast cancer survivors: a cross-cultural comparison

Abstract: Purpose Research in the area of cultural response pattern on questionnaires in the oncological setting and direct cross-cultural comparisons are lacking. This study examined response pattern in the reporting of depressive symptoms in Chinese and US women with breast cancer. We hypothesized that Chinese women are less likely to endorse positive affect items compared to their US counterparts. Additionally, we explored cultural differences in the association between positive affect and QOL. Methods Secondary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
9
0
2
Order By: Relevance
“…Moreover, the mean score of QOL value was much lower than that of patients with breast cancer in other developed countries. Milbury et al reported that the mean score of QOL was 104.12 ± 14.77 in USA during the year 2017 [ 45 ], Matthies et al reported a mean QOL score of 102.66 ± 22 in Germany during the year 2019 [ 46 ]. However, the mean QOL score observed in our investigation was closer to the Asian situation-the mean score of QOL in Korea was 91.26 ± 20.08 as reported by Park et al in 2019 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mean score of QOL value was much lower than that of patients with breast cancer in other developed countries. Milbury et al reported that the mean score of QOL was 104.12 ± 14.77 in USA during the year 2017 [ 45 ], Matthies et al reported a mean QOL score of 102.66 ± 22 in Germany during the year 2019 [ 46 ]. However, the mean QOL score observed in our investigation was closer to the Asian situation-the mean score of QOL in Korea was 91.26 ± 20.08 as reported by Park et al in 2019 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…China have a greater influence on their emotional well-being than do the low positive emotions of people with breast cancer in the United States (Milbury et al, 2017). Regardless of cultural differences (Shih, 1996), the HRQOL of people and their spouses in Asia probably differs from that of people and spouses in Western countries.…”
Section: Moreover the Low Positive Emotions Of People With Breast Camentioning
confidence: 99%
“…Previous studies on other types of cancer in China and the United States have shown that the overall HRQOL of people with breast cancer in China is lower than that of people with breast cancer in the United States (Lu et al., ). Moreover, the low positive emotions of people with breast cancer in China have a greater influence on their emotional well‐being than do the low positive emotions of people with breast cancer in the United States (Milbury et al., ). Regardless of cultural differences (Shih, ), the HRQOL of people and their spouses in Asia probably differs from that of people and spouses in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous surveys have found that those with high resilience shared common characteristics, for example, they experienced more positive affect (PA), optimism, hope, humour and curiosity when facing extreme adversity or trauma (Liu et al., ; Solano, da Silva, Soares, Ashmawi, & Vieira, ). Affect and its implications have been studied among cancer survivors, especially the importance of PA in QoL (Milbury et al., ; Moreno, Moskowitz, Ganz, & Bower, ). According to Fredrickson's broaden‐and‐build theory (Fredrickson, ), PA plays an important role in determining cognitive, physical and psychological activity.…”
Section: Introductionmentioning
confidence: 99%